INOVASI DESA WISATA KREATIF BERBASIS SPORT TOURISM - Alimuddin Alimuddin; Fahmil Haris Fahmil Haris; Donal Syafrianto Donal Syafrianto (Universitas Majalengka, 2022)
The tourism potential found in West Sumatra, especially in the Danau Kembar District area, is very much if developed properly, it can improve the economy and reduce community poverty. The area is surrounded by 3 lakes that stretch around the area. Job growth and economic growth can increase rapidly through tourism growth. However, the reality on the ground, many village Pokdarwis still complain about the lack of creativity in developing tourism and the tourism offered is still monotonous in certain photo spots. The purpose of implementing this service is to make the area a creative tourist location based on sports tourism. The implementation method is through training on the use and guidance of paddle as one of the creative tours based on sport tourism.